Global Reporting Initiative (GRI) and its Reflections in the Literature - Petr Petera; Jaroslav Wagner (European Financial and Accounting Journal, 2015)
Sustainability Reporting Guidelines published by the organization Global Reporting Initiative are gaining on importance and we were investigating whether this trend is also reflected in academic literature and if so, how. We conducted bibliometric analysis based on the Web of Science database to identify key articles, authors, journals and research topics. Results show that the amount of literature dealing with GRI Guidelines is growing. Major journals are Journal of Business Ethics, Corporate Social Responsibility and Environmental Management and Journal of Cleaner Production. High productive authors according to the number of authored or co-authored articles are Brown, H. S., Manetti, G., Evangelinos, K., Skouloudis, A., Searcy, C., Issac, B. and Modapothala, J. R. Research topics of these high productive authors are development of GRI as an institution, development of GRI Guidelines per se, methodologies for assessment of sustainability in organizations and composite indices, methodologies for evaluation and quality assessment of corporate responsibility reports, development of specific (e.g. sector-based) indicators and empirical investigation into indicators used in practice, stakeholder's role in the process of corporate responsibility reporting, assurance for corporate responsibility reports, exploring relation between quality of corporate sustainability disclosure and various variables, empirical content analysis and comparative content analysis of corporate sustainability reports and conceptual issues. We can conclude that the amount of relevant literature is growing and high productive authors and journals are emerging.
Keywords: M40; 650; Bibliometric analysis; Corporate social responsibility reporting; Global Reporting Initiative (GRI)